2010
DOI: 10.5222/terh.2010.25307
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome Among The Resident Doctors In Surgical And Nonsurgical Clinics

Abstract: AMAÇ: Cerrahi ve cerrahi dışı dallarda uzmanlık eğitimi alan asistan doktorların tükenmişlik sendromu açısından incelenerek, tükenmede rol alan etmenlerin değerlendirilmesi. Aıııılıtıır Sözciikleı·: Maslach Tükenmişlik Ölçeği, lvieslek hastalığı, Tıp Personeli, Tükenme Sendromu SUMMARY AIM: A fact-fınding study of bumout syndrome among assistant doctors who are specializing in internal and surgical and non-surgical clinics and evaluation of the causative factors involved. MATERIAL AND METHOD: lvlaslaclı Bumout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…When the participants of the study were grouped according to marital status it was seen that married physicians had significantly lower mean EE and D scores than those of single physicians, while their mean PA scores were significantly higher. Many studies conducted on the subject found no statistically significant differences between marital status variables and the mean scores for the sub-dimensions of burnout (6,7,8,(11)(12)(13)(14)(15). Some studies found that married ones had statistically significant lower mean EE and D scores than singles while their mean PA scores were found statistically higher, in line with the results of our study (9,16,17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When the participants of the study were grouped according to marital status it was seen that married physicians had significantly lower mean EE and D scores than those of single physicians, while their mean PA scores were significantly higher. Many studies conducted on the subject found no statistically significant differences between marital status variables and the mean scores for the sub-dimensions of burnout (6,7,8,(11)(12)(13)(14)(15). Some studies found that married ones had statistically significant lower mean EE and D scores than singles while their mean PA scores were found statistically higher, in line with the results of our study (9,16,17).…”
Section: Discussionsupporting
confidence: 90%
“…Studies conducted on this subject also found similar results (1,5,6). It was stated that the reason for this might have been related to the fact that non-surgical branches were selected more by women and, as studies have shown, women experienced emotional exhaustion more than men.…”
Section: Discussionsupporting
confidence: 63%